Literature Review: Strategi Penurunan Asupan Natrium Melalui Pengurangan Garam untuk Mencegah Hipertensi - Prasodjo, Regita Adjeng; Farapti, Farapti (Universitas Airlangga, 2024)
Background: The prevalence of hypertension is increasing globally year by year. The main risk factors for hypertension are lifestyle and high sodium diet. Sodium in food comes from salt. Salt is one of the ingredients commonly added to food to enhance the flavor of food. 1 gram of salt contains 40% sodium and 60% chloride. Sodium restriction through salt reduction needs to be implemented to prevent hypertension. Objectives: This literature review aims to identify strategies implemented in different countries to reduce average daily sodium intake through salt reduction. Methods: Article searched using PubMed and ScienceDirect databases with the results of screening articles that matched the criteria found 5 articles. After the article was obtained, articles were assessed and carried out to the stage of making a literature review. Results: There were 5 articles that discussed the strategies for implementing daily sodium restriction through salt reduction that have been implemented in various countries. These strategies included public nutrition education, salt taxation, high salt content labeling and logos on packaging, and food reformulation Conclusions: Strategies in several countries have been effective in limiting daily sodium through salt reduction. Nutrition education in the community is effective in increasing knowledge and understanding that leads to behavioral changes in salt reduction, salt taxation has the effect of decreasing consumer sales of high-salt packaged food products, and labeling and high salt content logos on packaging help consumers make low-salt food consumption choices, and food reformulation is used as a way to increase accessibility of low-salt foods.